Gestão do conhecimento na administração pública e uso de tecnologia da informação para melhoria dos resultados: o caso do Corpo de Intendentes da Marinha - Campos, Samuel Vasconcelos (2014)
We live in a society increasingly globalized, attentive, informed and demanding for services provided by public and private organizations. The current available technology, for a growing number of people, in real time, provide a huge set of information, opinions and allows them to interact with people from different cultures and, disregarding the distances they are, link them in ways never experienced before. The influence of technology has brought such deep consequences to our lifestyle that, every new invention, enables new experiences can be enjoyed and words like innovation, reinvention and change are constantly on the agenda. In this context, knowledge management is becoming increasingly important in organizations environments, linking right people and developing new knowledge that make it easier to deal with these constant changes and consequent insecurities generated. This study checked what the Knowledge Management level is conducted within a Brazilian federal government, the Brazilian Navy, and specifically in its Supply Officer Body, was measured in eight of its main military organizations through qualitative and quantitative methods, how this tool has been used. At the end, by propositional form, based on the results of the assessment and literature review, it was suggested a framework of knowledge management, in order to improve the current knowledge management levels detected in a such way, that allows undertaken actions be more effectual, efficient and effective, hence, contributing to development of these organizations.